Being Surprised by the Unsurprising: Earnings Seasonality and Stock Returns - Chang, Tom Y.; Hartzmark, Samuel M.; Solomon, David H.; Soltes, Eugene F. (Review of Financial Studies, 2017)
We present evidence consistent with markets failing to properly price information in seasonal earnings patterns. Firms with historically larger earnings in one quarter of the year (“positive seasonality quarters”) have higher returns when those earnings are usually announced. Analysts have more positive forecast errors in positive seasonality quarters, consistent with the returns being driven by mistaken earnings estimates. We show that investors appear to overweight recent lower earnings following positive seasonality quarters, leading to pessimistic forecasts in the subsequent positive seasonality quarter. The returns are not explained by risk-based explanations, firm-specific information, increased volume, or idiosyncratic volatility. Received June 19, 2014; accepted April 25, 2016, by Editor David Hirshleifer.